Hydrotalcite material as well as preparation method and application thereof
Large-sized hydrotalcite materials were prepared by colloid grinding nucleation reaction and dropping reaction methods. Combined with the use of anionic polymer and high-polar polymer, the problem of poor gas barrier performance of existing hydrotalcite materials was solved, and the preparation of high-performance gas barrier films was realized.
Patent Information
- Application Number
- CN202411663354.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The size of existing hydrotalcite materials is small, resulting in poor gas barrier properties. The preparation of large-sized hydrotalcite sheets faces challenges and is difficult to achieve large-scale application.
Hydral talc materials were prepared by colloid grinding nucleation reaction and dropwise reaction methods, and the planar size of hydrotalc was increased by using anionic polymer and highly polar polymers, and their performance was improved by ion exchange and anti-aging agent intercalation modification.
The prepared hydrotalcite material has a larger planar size, which significantly improves gas barrier properties and anti-aging properties, and is suitable for the preparation of high-performance gas barrier films.
Smart Images

Figure CN119503850A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic / organic composite thin film functional materials, and in particular to a hydrotalcite material and a preparation method and application thereof. Background Art
[0002] Polyurethane is widely used in food packaging, transportation, construction, aerospace and other fields, and plays an important role in the national economy. In the fields of aerospace, packaging and other fields, the gas barrier performance and aging resistance of the material are crucial. However, due to the low atomic packing density of polymer materials and a certain free volume, gas molecules can penetrate slowly, resulting in poor gas barrier performance. In recent years, people have found that flaky inorganic fillers such as clay and graphene can effectively improve the gas barrier performance of polymer materials. The working principle is that the "maze effect" formed by the flaky filler effectively prolongs the diffusion path of the gas in the polymer matrix. However, the preparation process of graphene is complicated, the size of clay is difficult to control, and its function is relatively single. There are still many problems in the application, and it is difficult to achieve large-scale application. In addition, there are still problems such as difficulty in controlling particle size and low compatibility between fillers and polymers. In addition, polyurethane will age and degrade under light, heat and oxygen environments, resulting in the deterioration of the physical properties of polyurethane and failure.
[0003] Two-dimensional anionic layered materials such as hydrotalcites (LDHs) have attracted widespread attention due to their greater composition and structural controllability. LDHs are compounds formed by the stacking of interlayer anions and positively charged layers, and have the characteristics of adjustable layer metal element ratios and exchangeable interlayer anions. Compared with other inorganic fillers and functional additives, hydrotalcites have more advantages in functionality. In recent years, people have found that hydrotalcites have good gas barrier properties. Reference Chem. Eng. Sci., 2023, 280, 119016 A hybrid film of layered double hydroxide modified with sodium dodecyl sulfate and poly (butylene adipate-terephthalate) was prepared by layer-by-layer self-assembly. The results show that the two-dimensional layered structure of hydrotalcite hinders the diffusion of gas molecules and greatly reduces the oxygen permeability. Reference RSC Adv., 2016, 6, 34288 Dodecylsulfonate intercalated magnesium aluminum layered double hydroxide was mixed with polyurethane to form a nanocomposite material. The study found that intercalated hydrotalcite significantly improved the mechanical properties of polyurethane. However, the prepared hydrotalcite had a small particle size, poor gas barrier properties, and poor anti-aging properties.
[0004] CN112724463A adopts a hydrothermal method and an ion exchange method to prepare tannic acid-modified hydrotalcite, and then assembles the hydrotalcite with polyethylene oxide through a layer-by-layer self-assembly method to prepare a stretchable gas barrier film with excellent gas barrier properties. However, the prepared hydrotalcite is small in size, and the layer-by-layer self-assembly method has complicated operation steps, which has great limitations in preparing larger-sized films and is still unable to be industrially applied.
[0005] CN104817710A uses suction filtration deposition film-forming technology to composite hydrotalcite with a two-dimensional layered structure and various commercial packaging polymer raw materials into films, and uses the orderly stacking of hydrotalcite to extend the diffusion path of gas molecules in the composite film, thereby further improving the barrier properties of the film material. However, the prepared hydrotalcite is small in size, and the suction filtration deposition film-forming technology is also difficult to apply on a large scale.
[0006] It can be seen that the size of the hydrotalcite sheets currently prepared is small, and it is usually necessary to use methods such as layer-by-layer self-assembly to arrange the hydrotalcite sheets regularly to improve the gas barrier properties of the film. When hydrotalcite is directly added to the film matrix, the hydrotalcite sheets are irregularly arranged in the film, and the gas barrier properties will be greatly reduced. At this time, the size of the hydrotalcite sheets will determine the gas barrier properties of the film. Therefore, the preparation of large-sized hydrotalcite sheets is crucial for its practical application in gas barrier. However, the preparation of functional large-sized hydrotalcite sheets still faces great challenges. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a hydrotalcite material and a preparation method and application thereof.
[0008] In order to achieve the above object, the present invention provides a method for preparing a hydrotalcite material in a first aspect, wherein the method comprises the following steps:
[0009] (1) subjecting the first mixed salt solution and the alkaline solution to a colloidal grinding nucleation reaction to obtain a hydrotalcite seed slurry;
[0010] (2) mixing the second mixed salt solution, the slow-release precipitant, the anionic high molecular polymer and the high polarity polymer to obtain a mixed solution;
[0011] (3) adding the mixed solution obtained in step (2) dropwise to the hydrotalcite seed slurry obtained in step (1) to react and obtain a hydrotalcite material;
[0012] Wherein, the first mixed salt solution and the second mixed salt solution both contain soluble divalent metal salts and soluble trivalent metal salts, and the types and concentrations of the metal salts are the same.
[0013] The second aspect of the present invention provides a hydrotalcite material or a modified hydrotalcite material obtained according to the preparation method described in the first aspect.
[0014] The third aspect of the present invention provides use of the hydrotalcite material or modified hydrotalcite material described in the second aspect in preparing a gas barrier film.
[0015] A fourth aspect of the present invention provides a polyurethane gas barrier film comprising the hydrotalcite material or the modified hydrotalcite material according to the second aspect.
[0016] The fifth aspect of the present invention provides a method for preparing the polyurethane gas barrier film according to the fourth aspect, wherein the method comprises: mixing a hydrotalcite material or a modified hydrotalcite material with a polyurethane dispersion, and drying to obtain the polyurethane gas barrier film.
[0017] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0018] (1) The hydrotalcite material provided by the present invention has a larger plane size. When added as a functional additive to a polymer matrix (such as polyurethane), it can effectively extend the diffusion path of the gas in the film and improve the gas barrier performance;
[0019] (2) After the anti-aging agent intercalation modification, the anti-aging performance of the polymer matrix (such as polyurethane) can be significantly improved, thereby increasing the service life of the polyurethane film;
[0020] (3) The hydrotalcite material of the present invention has good compatibility with polyurethane and can be directly added to the matrix while ensuring excellent gas barrier properties;
[0021] (4) The preparation method of the hydrotalcite material of the present invention is simple, the raw material source is extensive and abundant, the cost is low, and it is convenient for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the XRD spectrum of MgAl-DBHP-LDH obtained in Example 1 of the present invention.
[0023] Figure 2 This is the FT-IR spectrum of MgAl-DBHP-LDH obtained in Example 1 of the present invention.
[0024] Figure 3 This is a SEM photograph of MgAl-DBHP-LDH obtained in Example 1 of the present invention.
[0025] Figure 4 This is the XRD spectrum of the polyurethane composite film obtained in Example 1 of the present invention.
[0026] Figure 5 This is the FT-IR spectrum of the polyurethane composite film obtained in Example 1 of the present invention.
[0027] Figure 6 This is a SEM photograph of the polyurethane composite film obtained in Example 1 of the present invention.
[0028] Figure 7 This is the gas barrier performance of the polyurethane composite film obtained in Example 1 of the present invention.
[0029] Figure 8 This is a graph showing the aging resistance of the polyurethane composite film obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] A first aspect of the present invention provides a method for preparing a hydrotalcite material, wherein the method comprises the following steps:
[0032] (1) subjecting the first mixed salt solution and the alkaline solution to a colloidal grinding nucleation reaction to obtain a hydrotalcite seed slurry;
[0033] (2) mixing the second mixed salt solution, the slow-release precipitant, the anionic high molecular polymer and the high polarity polymer to obtain a mixed solution;
[0034] (3) adding the mixed solution obtained in step (2) dropwise to the hydrotalcite seed slurry obtained in step (1) to react and obtain a hydrotalcite material;
[0035] Wherein, the first mixed salt solution and the second mixed salt solution both contain soluble divalent metal salts and soluble trivalent metal salts, and the types and concentrations of the metal salts are the same.
[0036] The present invention obtains hydrotalcite seeds by firstly performing a colloid grinding nucleation reaction, and then adding a salt solution to make them continue to grow; in addition, by adding anionic high molecular polymers and high polar polymers, the plane size of the hydrotalcite material can be further increased, and the further increase of the thickness can be inhibited. The hydrotalcite material prepared by the present invention is used to prepare a gas barrier film, and its gas barrier performance can be further improved.
[0037] In some embodiments of the present invention, in the first mixed salt solution and the second mixed salt solution, the divalent metal cation M in the soluble divalent metal salt 2+ The trivalent metal cation M in the soluble trivalent metal salt 3+ The molar ratio is 2-4:1.
[0038] In some embodiments of the present invention, the solvent of the first mixed salt solution and the second mixed salt solution is deionized water containing 5-50 vol% tetrahydrofuran.
[0039] In some embodiments of the present invention, the divalent metal cation M 2+ The concentration is 0.2-2mol / L.
[0040] In some embodiments of the present invention, the divalent metal cation M 2+ Mg 2+ or Zn 2+ .
[0041] In some embodiments of the present invention, the trivalent metal cation M 3+ For Al 3+ .
[0042] In some embodiments of the present invention, the volume ratio of the first mixed salt solution to the second mixed salt solution is 1:3-6.
[0043] In some embodiments of the present invention, in step (1), the molar ratio of the alkali in the alkaline solution to the metal cation in the first mixed salt solution is 2:1.
[0044] In some embodiments of the invention, the base is sodium hydroxide.
[0045] In some embodiments of the present invention, the hydrotalcite seed slurry in step (1) is heated to 100-140°C.
[0046] In some embodiments of the present invention, in step (2), the slow-release precipitant is hexamethylenetetramine and / or urea.
[0047] In some embodiments of the present invention, the anionic high molecular polymer is at least one selected from sodium polyacrylate, sodium polystyrene sulfonate and sodium polymethacrylate.
[0048] In some embodiments of the present invention, the weight average molecular weight of the anionic high molecular polymer is 1000-20000.
[0049] In some embodiments of the present invention, the high polarity polymer is selected from at least one of polyethylene glycol, polyacrylamide, hydroxymethyl cellulose and polydopamine.
[0050] In some embodiments of the present invention, the slow-release precipitant and the trivalent metal cation M in the soluble trivalent metal salt 3+ The molar ratio is 4-10:1.
[0051] In some embodiments of the present invention, the concentration of the anionic high molecular polymer is 5-50 g / L, preferably 6.7-20 g / L, and more preferably 15-16 g / L.
[0052] In some embodiments of the present invention, the concentration of the high polarity polymer is 2-40 g / L, preferably 5-16.7 g / L, and more preferably 9-12 g / L.
[0053] In some embodiments of the present invention, in step (3), the dropping time is 6-10 hours.
[0054] In some embodiments of the present invention, after the dropwise addition is completed, the temperature is raised to 140-180° C. and the reaction is continued for 6-8 hours.
[0055] In some embodiments of the present invention, after the reaction is completed, the mixture is cooled to room temperature and the precipitate is washed to obtain a hydrotalcite material.
[0056] In some embodiments of the present invention, the method further comprises:
[0057] (4) dispersing the hydrotalcite material obtained in step (3) in a mixed solution containing a strong acid and its salt to carry out an ion exchange reaction to obtain a corresponding acid radical hydrotalcite material. After the ion exchange, the carbonate ions between the hydrotalcite layers are replaced by strong acid ions, thereby expanding the interlayer spacing and facilitating subsequent intercalation modification.
[0058] In some embodiments of the present invention, the amount of the hydrotalcite material is 10-30 g / L.
[0059] In some embodiments of the present invention, in the mixed solution containing a strong acid and a salt thereof, the concentration of the strong acid is 0.001-0.005 mol / L.
[0060] In some embodiments of the present invention, in the mixed solution containing a strong acid and a salt thereof, the concentration of the salt is 0.2-2 mol / L.
[0061] In some embodiments of the present invention, the strong acid is nitric acid or hydrochloric acid.
[0062] In some embodiments of the present invention, the salt is selected from at least one of an ammonium salt, a sodium salt and a potassium salt.
[0063] In some embodiments of the present invention, the conditions for the ion exchange reaction include: stirring; time is 12-24 hours.
[0064] In some embodiments of the present invention, the method further comprises:
[0065] (5) dispersing the hydrotalcite material obtained in step (4) in an antioxidant solution, and reacting to obtain a modified hydrotalcite material.
[0066] In some embodiments of the present invention, the concentration of the antioxidant solution is 1-2 mol / L.
[0067] In some embodiments of the present invention, the antioxidant is selected from at least one of p-methoxycinnamic acid, salicylic acid, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, coumarin-3-carboxylic acid, cinnamic acid, benzotriazole-4-hydroxy-benzenesulfonic acid, 2-phenylbenzimidazole-5-sulfonic acid and 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid.
[0068] In some embodiments of the present invention, the solvent of the antioxidant solution is formamide.
[0069] In some embodiments of the present invention, the molar ratio of the antioxidant to the anions between the layers of the hydrotalcite material is 1-4:1.
[0070] In some embodiments of the present invention, the reaction conditions include: stirring; temperature of 80-120° C.; time of 3-12 h.
[0071] According to a particularly preferred embodiment of the present invention, a method for preparing a hydrotalcite material comprises the following steps:
[0072] (1) dissolving a soluble divalent metal salt and a trivalent metal salt in deionized water containing 5-50 vol% tetrahydrofuran to prepare a first mixed salt solution, wherein the divalent metal cation M 2+ With trivalent metal cation M 3+ The molar ratio is 2-4:1, M 2 + The concentration is 0.2-2mol / L; prepare sodium hydroxide alkaline solution, sodium hydroxide and (M 2+ +M 3+ ) has a molar ratio of 2:1; adding the salt solution and the alkaline solution to the colloid mill at the same time to react to obtain a hydrotalcite seed slurry, transferring the hydrotalcite seed slurry to a reactor, and heating to 100-140° C.;
[0073] (2) preparing a second mixed salt solution with the same concentration as that in step (1), wherein the volume thereof is 3-6 times the volume of the first mixed salt solution; adding a slow-release precipitant, an anionic high molecular polymer and a high polar polymer and stirring to obtain a mixed solution, wherein the slow-release precipitant and the trivalent metal cation M 3+The molar ratio is 4-10:1; wherein the concentration of the anionic high molecular polymer is 5-50 g / L, and the concentration of the high polar polymer is 2-40 g / L; the mixed solution is added dropwise to the reactor in step (1) for 6-10 hours, and after the addition is completed, the temperature is raised to 140-180° C. and the reaction is continued for 6-8 hours, and after the reaction is completed, the temperature is cooled to room temperature; the precipitate is washed to obtain a carbonate-type hydrotalcite material;
[0074] (3) dispersing the hydrotalcite material obtained in step (2) in a mixed solution containing a strong acid and its salt, wherein the content of the hydrotalcite is 10-30 g / L, stirring the mixture for 12-24 h, and after the ion exchange reaction is completed, washing the mixture to obtain the corresponding acid radical hydrotalcite material;
[0075] (4) dissolving an antioxidant in formamide to prepare a solution so that the concentration of the antioxidant is 1-2 mol / L; dispersing the hydrotalcite material obtained in step (3) in the solution so that the molar ratio of the antioxidant to the hydrotalcite interlayer anion is 1-4:1, stirring the reaction at 80-120° C. for 3-12 hours, washing and drying to obtain the modified hydrotalcite material.
[0076] The second aspect of the present invention provides a hydrotalcite material or a modified hydrotalcite material obtained according to the preparation method described in the first aspect.
[0077] In some embodiments of the present invention, the size of the hydrotalcite material or modified hydrotalcite material is 2-10 μm. In the present invention, the "size" refers to the plane size, that is, the particle size.
[0078] The third aspect of the present invention provides use of the hydrotalcite material or modified hydrotalcite material described in the second aspect in preparing a gas barrier film.
[0079] In some embodiments of the present invention, the substrate of the gas barrier film is selected from at least one of polyurethane, polyvinyl chloride, polylactic acid, polypropylene and nitrile rubber.
[0080] A fourth aspect of the present invention provides a polyurethane gas barrier film comprising the hydrotalcite material or the modified hydrotalcite material according to the second aspect.
[0081] In some embodiments of the present invention, the content of the hydrotalcite material or modified hydrotalcite material in the film is 1-10 wt %.
[0082] The fifth aspect of the present invention provides a method for preparing the polyurethane gas barrier film according to the fourth aspect, wherein the method comprises: mixing a dispersion of a hydrotalcite material or a modified hydrotalcite material with a polyurethane dispersion, and drying to obtain the polyurethane gas barrier film.
[0083] In some embodiments of the present invention, the mixing conditions include: temperature of 40-60° C.; time of 2-4 h.
[0084] In some embodiments of the present invention, the solvent of the polyurethane dispersion is tetrahydrofuran or dimethyltetrahydrofuran.
[0085] The present invention will be described in detail below through examples.
[0086] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0087] Sources:
[0088] Sodium polyacrylate: Macklin 767418 average Mw 2100;
[0089] Polyethylene glycol: JESK KA672876average Mw 100000;
[0090] Sodium polystyrene sulfonate: JESK KA742272 analytical standard, for GPC, average Mw17000;
[0091] Sodium polymethacrylate: Macklin S902410Mw 4,000-6,000;
[0092] Polyacrylamide: Macklin 62649-23-4Mw 520,000;
[0093] Polyurethane: Polyurethane was provided by Liming Chemical Design and Research Institute Co., Ltd., Mn60,000-70,000.
[0094] Example 1
[0095] This example is used to illustrate the preparation of hydrotalcite material.
[0096] (1) 6.4103 g of Mg(NO3)2·6H2O and 4.6891 g of Al(NO3)2·6H2O were weighed and dissolved in 50 mL of deionized water containing 25 vol% of tetrahydrofuran to prepare a first mixed salt solution; 3 g of NaOH was weighed and dissolved in 50 mL of deionized water to prepare an alkaline solution; the first mixed salt solution and the alkaline solution were simultaneously added to a colloid mill for nucleation reaction to obtain a hydrotalcite seed slurry, which was then transferred to a reactor and heated to 100° C.;
[0097] (2) preparing 300 mL of a second mixed salt solution (the type and concentration of the salt are the same as those of the first mixed salt solution), adding 8.7618 g of hexamethylenetetramine, 2 g of sodium polyacrylate (6.7 g / L) and 1.5 g of polyethylene glycol (5 g / L), and stirring to obtain a mixed solution; dropping the mixed solution into a reactor for 6 h, and continuing to heat to 180 ° C for 6 h after the addition is completed. After cooling, the precipitate is washed several times with deionized water and ethanol to obtain hydrotalcite, which is recorded as MgAl-CO3-LDH;
[0098] (3) 5 g of MgAl-CO3-LDH was added to 400 mL of a nitrate-containing solution (42.5 g of NaNO3 and 145.4 μL of HNO3), and stirred for 24 h under nitrogen protection. After washing with deionized water and ethanol several times, MgAl-NO3-LDH was obtained;
[0099] (4) 5 g of MgAl-NO3-LDH was added to 20 mL of formamide solution containing 5 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid (DBHP), stirred at 80 °C under nitrogen protection for 4 h, washed several times with deionized water and ethanol, and dried to obtain MgAl-DBHP-LDH.
[0100] Example 2
[0101] This example is used to illustrate the preparation of hydrotalcite material.
[0102] (1) 7.6923 g of Mg(NO3)2·6H2O and 5.6270 g of Al(NO3)2·6H2O were weighed and dissolved in 50 mL of deionized water containing 15 vol% of tetrahydrofuran to prepare a first mixed salt solution; 3.6 g of NaOH was weighed and dissolved in 50 mL of deionized water to prepare an alkaline solution; the first mixed salt solution and the alkaline solution were simultaneously added to a colloid mill for nucleation reaction to obtain a hydrotalcite seed slurry, which was then transferred to a reactor and heated to 100° C.;
[0103] (2) preparing 200 mL of a second mixed salt solution (the type and concentration of the salt are the same as those of the first mixed salt solution), adding 10.5143 g of urea, 3 g of sodium polystyrene sulfonate (15 g / L) and 1.8 g of polyethylene glycol (9 g / L), stirring evenly to obtain a mixed solution, and dripping the mixed solution into a reactor for 8 h. After the dripping is completed, heating to 160 ° C and continuing the reaction for 6 h. After cooling, washing the precipitate with deionized water and ethanol several times to obtain hydrotalcite, recorded as MgAl-CO3-LDH;
[0104] (3) 6 g of MgAl-CO3-LDH was added to 400 mL of a chloride ion solution (30 g of NaCl and 150 μL of HCl) and stirred for 24 h under nitrogen protection. After washing with deionized water and ethanol several times, MgAl-Cl-LDH was obtained.
[0105] (4) 5 g of MgAl-Cl-LDH was added to 30 mL of formamide solution containing 5 g of 2-phenylbenzimidazole-5-sulfonic acid (PSA), stirred at 80 °C under nitrogen protection for 4 h, washed with deionized water and ethanol several times, and dried to obtain MgAl-PSA-LDH.
[0106] Example 3
[0107] This example is used to illustrate the preparation of hydrotalcite material.
[0108] (1) Weighing 12.8205 g of Mg(NO3)2·6H2O and 9.3783 g of Al(NO3)2·6H2O and dissolving them in 50 mL of deionized water containing 20 vol% of tetrahydrofuran to prepare a first mixed salt solution; weighing 6 g of NaOH and dissolving them in 50 mL of deionized water to prepare an alkaline solution; adding the first mixed salt solution and the alkaline solution simultaneously to a colloid mill for nucleation reaction to obtain a hydrotalcite seed slurry, which is then transferred to a reactor and heated to 100°C;
[0109] (2) preparing 250 mL of a second mixed salt solution (the type and concentration of the salt are the same as those of the first mixed salt solution), adding 15 g of hexamethylenetetramine, 4 g of sodium polymethacrylate (16 g / L) and 3 g of polyacrylamide (12 g / L), and stirring to obtain a mixed solution; dropping the mixed solution into a reactor for 7 h, heating to 150 ° C after the addition is completed and continuing the reaction for 8 h, and washing the precipitate with deionized water and ethanol several times after cooling to obtain hydrotalcite, recorded as MgAl-CO3-LDH;
[0110] (3) 5 g of MgAl-CO3-LDH was added to 400 mL of a nitrate-containing solution (50 g of NaNO3 and 160 μL of HNO3), and stirred for 24 h under nitrogen protection. After washing with deionized water and ethanol several times, MgAl-NO3-LDH was obtained.
[0111] (4) 5 g of MgAl-NO3-LDH was added to 20 mL of formamide solution containing 3 g of salicylic acid (SA), stirred at 90 °C under nitrogen protection for 3 h, washed several times with deionized water and ethanol, and dried to obtain MgAl-SA-LDH.
[0112] Example 4
[0113] This example is used to illustrate the preparation of hydrotalcite material.
[0114] (1) 15.3846 g of Mg(NO3)2·6H2O and 11.2539 g of Al(NO3)2·6H2O were weighed and dissolved in 50 mL of deionized water containing 35 vol% of tetrahydrofuran to prepare a first mixed salt solution; 2.4 g of NaOH was weighed and dissolved in 50 mL of deionized water to prepare an alkaline solution; the first mixed salt solution and the alkaline solution were simultaneously added to a colloid mill for nucleation reaction to obtain a hydrotalcite seed slurry, which was then transferred to a reactor and heated to 100° C.;
[0115] (2) preparing 300 mL of a second mixed salt solution (the type and concentration of salt are the same as those of the first mixed salt solution), adding 19 g of urea, 6 g of sodium polyacrylate (20 g / L) and 5 g of polyacrylamide (16.7 g / L), and stirring to obtain a mixed solution; dropping the mixed solution into a reactor for 6 h, heating to 180 °C after the addition is completed and continuing the reaction for 6 h, and washing the precipitate with deionized water and ethanol several times after cooling to obtain hydrotalcite, recorded as MgAl-CO3-LDH;
[0116] (3) 5 g of MgAl-CO3-LDH was added to 400 mL of a chloride ion solution (48 g of NaCl and 160 μL of HCl), and stirred for 24 h under nitrogen protection. After washing with deionized water and ethanol several times, MgAl-Cl-LDH was obtained.
[0117] (4) 5 g of MgAl-Cl-LDH was added to 20 mL of formamide solution containing 5.6 g of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (UVBP-4), stirred at 90 °C under nitrogen protection for 3 h, washed several times with deionized water and ethanol, and dried to obtain MgAl-UVBP-4-LDH.
[0118] Example 5
[0119] This example is used to illustrate the preparation of hydrotalcite material.
[0120] (1) 6.4103 g of Mg(NO3)2·6H2O and 4.6891 g of Al(NO3)2·6H2O were weighed and dissolved in 50 mL of deionized water containing 25 vol% of tetrahydrofuran to prepare a first mixed salt solution; 3 g of NaOH was weighed and dissolved in 50 mL of deionized water to prepare an alkaline solution; the first mixed salt solution and the alkaline solution were simultaneously added to a colloid mill for nucleation reaction to obtain a hydrotalcite seed slurry, which was then transferred to a reactor and heated to 100° C.;
[0121] (2) preparing 300 mL of a second mixed salt solution (the type and concentration of the salt are the same as those of the first mixed salt solution), adding 8.7618 g of hexamethylenetetramine, 1 g of sodium polyacrylate (3.3 g / L) and 0.5 g of polyethylene glycol (1.7 g / L), and stirring to obtain a mixed solution; dropping the mixed solution into a reactor for 6 h, and continuing to heat to 180 ° C for 6 h after the addition is completed. After cooling, the precipitate is washed several times with deionized water and ethanol to obtain hydrotalcite, which is recorded as MgAl-CO3-LDH;
[0122] (3) 5 g of MgAl-CO3-LDH was added to 400 mL of a nitrate-containing solution (42.5 g of NaNO3 and 145.4 μL of HNO3), and stirred for 24 h under nitrogen protection. After washing with deionized water and ethanol several times, MgAl-NO3-LDH was obtained;
[0123] (4) 5 g of MgAl-NO3-LDH was added to 20 mL of formamide solution containing 5 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid (DBHP), stirred at 80 °C under nitrogen protection for 4 h, washed several times with deionized water and ethanol, and dried to obtain MgAl-DBHP-LDH.
[0124] Example 6
[0125] This example is used to illustrate the preparation of hydrotalcite material.
[0126] (1) Weighing 6.4103 g of Mg(NO3)2·6H2O and 4.6891 g of Al(NO3)2·6H2O and dissolving them in 50 mL of 25 vol% tetrahydrofuran-containing deionized water to prepare a first mixed salt solution; weighing 3 g of NaOH and dissolving them in 50 mL of deionized water to prepare an alkaline solution; adding the first mixed salt solution and the alkaline solution simultaneously to a colloid mill for nucleation reaction to obtain a hydrotalcite seed slurry, which is then transferred to a reactor and heated to 100° C.;
[0127] (2) preparing 300 mL of a second mixed salt solution (the type and concentration of the salt are the same as those of the first mixed salt solution), adding 8.7618 g of hexamethylenetetramine, 20 g of sodium polyacrylate (67 g / L) and 15 g of polyethylene glycol (50 g / L), and stirring to obtain a mixed solution; dropping the mixed solution into a reactor for 6 h, and continuing to heat to 180 ° C for 6 h after the addition is completed. After cooling, the precipitate is washed several times with deionized water and ethanol to obtain hydrotalcite, which is recorded as MgAl-CO3-LDH;
[0128] (3) 5 g of MgAl-CO3-LDH was added to 400 mL of a nitrate-containing solution (42.5 g of NaNO3 and 145.4 μL of HNO3), and stirred for 24 h under nitrogen protection. After washing with deionized water and ethanol several times, MgAl-NO3-LDH was obtained;
[0129] (4) 5 g of MgAl-NO3-LDH was added to 20 mL of formamide solution containing 5 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid (DBHP), stirred at 80 °C under nitrogen protection for 4 h, washed several times with deionized water and ethanol, and dried to obtain MgAl-DBHP-LDH.
[0130] Comparative Example 1
[0131] MgAl-DBHP-LDH was prepared according to the method of Example 1, except that polyethylene glycol was not added in step (2).
[0132] Comparative Example 2
[0133] MgAl-DBHP-LDH was prepared according to the method of Example 1, except that sodium polyacrylate and polyethylene glycol were not added in step (2).
[0134] Application Example 1
[0135] 3 g of polyurethane was dissolved in 20 mL of tetrahydrofuran to obtain a polyurethane dispersion; 0.15 g of MgAl-DBHP-LDH obtained in Example 1 was dispersed in 15 mL of tetrahydrofuran solution and subjected to ultrasonic treatment to obtain a dispersion; the dispersions were mixed, mechanically stirred at 60° C. for 3 h, cooled to remove bubbles, and the mixture was transferred to a molded template. After drying, a gas barrier film material composited with hydrotalcite and polyurethane was obtained.
[0136] Application Example 2
[0137] 3 g of polyurethane was dissolved in 20 mL of tetrahydrofuran to obtain a polyurethane dispersion; 0.15 g of MgAl-PSA-LDH obtained in Example 2 was dispersed in 15 mL of tetrahydrofuran solution and subjected to ultrasonic treatment to obtain a dispersion; the dispersions were mixed, mechanically stirred at 60° C. for 3 h, cooled to remove bubbles, and the mixture was transferred to a molded template. After drying, a gas barrier film material composited with hydrotalcite and polyurethane was obtained.
[0138] Application Example 3
[0139] 3 g of polyurethane was dissolved in 20 mL of tetrahydrofuran to obtain a polyurethane dispersion; 0.15 g of MgAl-SA-LDH obtained in Example 3 was dispersed in 15 mL of tetrahydrofuran solution and subjected to ultrasonic treatment to obtain a dispersion; the dispersions were mixed and mechanically stirred at 60° C. for 3 h. After cooling to eliminate bubbles, the mixed solution was transferred to a molded template and dried to obtain a gas barrier film material composited with hydrotalcite and polyurethane.
[0140] Application Example 4
[0141] 3 g of polyurethane was dissolved in 20 mL of tetrahydrofuran to obtain a polyurethane dispersion; 0.15 g of MgAl-UVBP-4-LDH obtained in Example 4 was dispersed in 15 mL of tetrahydrofuran solution and subjected to ultrasonic treatment to obtain a dispersion; the dispersions were mixed, mechanically stirred at 60° C. for 3 h, cooled to remove bubbles, and the mixed solution was transferred to a molded template. After drying, a gas barrier film material composited with hydrotalcite and polyurethane was obtained.
[0142] Application Example 5
[0143] 3 g of polyurethane was dissolved in 20 mL of tetrahydrofuran to obtain a polyurethane dispersion; 0.15 g of MgAl-DBHP-LDH obtained in Example 5 was dispersed in 15 mL of tetrahydrofuran solution and subjected to ultrasonic treatment to obtain a dispersion; the dispersions were mixed and mechanically stirred at 60° C. for 3 h. After cooling to eliminate bubbles, the mixed solution was transferred to a molded template and dried to obtain a gas barrier film material composited with hydrotalcite and polyurethane.
[0144] Application Example 6
[0145] 3 g of polyurethane was dissolved in 20 mL of tetrahydrofuran to obtain a polyurethane dispersion; 0.15 g of MgAl-DBHP-LDH obtained in Example 6 was dispersed in 15 mL of tetrahydrofuran solution and subjected to ultrasonic treatment to obtain a dispersion; the dispersions were mixed and mechanically stirred at 60° C. for 3 h. After cooling to eliminate bubbles, the mixed solution was transferred to a molded template and dried to obtain a gas barrier film material composited with hydrotalcite and polyurethane.
[0146] Application Comparative Example 1
[0147] A gas barrier film material was prepared according to the method of Application Example 1, except that the MgAl-DBHP-LDH obtained in Example 1 was replaced by the MgAl-DBHP-LDH obtained in Comparative Example 1.
[0148] Application Comparative Example 2
[0149] A gas barrier film material was prepared according to the method of Application Example 1, except that the MgAl-DBHP-LDH obtained in Example 1 was replaced by the MgAl-DBHP-LDH obtained in Comparative Example 2.
[0150] Test Example 1
[0151] Figure 1-3 The XRD, FT-IR and SEM images of MgAl-DBHP-LDH prepared in Example 1 are shown respectively.
[0152] Depend on Figure 1 It can be seen that the (003) characteristic peak of MgAl-CO3-LDH moved from 11.7° to 3.44°, and the corresponding interlayer spacing expanded from 0.76 nm to 2.57 nm, confirming the successful synthesis of MgAl-DBHP-LDH.
[0153] Depend on Figure 2 It can be seen that COO in DBHP - The asymmetric stretching vibration peak at 1708 cm -1 Move to 1547cm -1 , the symmetrical stretching vibration peak is from 1433cm -1 Move to 1407cm -1 , indicating that there is an interaction between the DBHP guest anion and the positively charged LDH host layer.
[0154] Depend on Figure 3 It can be seen that MgAl-DBHP-LDH presents a regular hexagonal sheet structure with a particle size distribution of 6-13.5 μm, while the particle size distribution of MgAl-DBHP-LDH prepared in Comparative Example 1 is 2-4 μm, and the particle size distribution of MgAl-DBHP-LDH prepared in Comparative Example 2 is 1-2 μm.
[0155] Test Example 2
[0156] Figure 4-6 The XRD, FT-IR and SEM images of the gas barrier film material composited with hydrotalcite and polyurethane prepared in Example 1 are shown respectively.
[0157] Depend on Figure 4 It can be seen that the peak of the film material is a superposition of the peaks of MgAl-DBHP-LDH and PU, which further proves the composition of the two-dimensional composite film. Compared with the MgAl-DBHP-LDH powder sample, there is no non-basal reflection (h, l≠0), which indicates that the preferred parallel orientation of MgAl-DBHP-LDH in the film is beneficial to improve the gas barrier performance.
[0158] Depend on Figure 5 It can be seen that after forming the film material, COO - The asymmetric stretching vibration peak from 1719cm -1 Move to 1582cm -1, indicating that there are hydrogen bonding and other interactions between PU and MgAl-DBHP-LDH.
[0159] Depend on Figure 6 It can be seen that MgAl-DBHP-LDH has good dispersibility in PU.
[0160] Test Example 3
[0161] The gas barrier properties of the gas barrier film materials prepared in Application Examples 1-6 were tested:
[0162] OTR was measured at room temperature using a C101H gas permeability tester (Labthink, China) based on the differential pressure method. The barrier film was placed in the middle of the upper and lower chambers. O2 molecules would diffuse from the high-pressure chamber through the film to the low-pressure chamber.
[0163] Depend on Figure 7 It can be seen that the addition of MgAl-DBHP-LDH obtained in Example 1 into PU improves its gas barrier properties, and the oxygen permeability is 1960.3072 cm 3 / m 2 ·24h·0.1MPa, an increase of ~56%.
[0164] Test Example 4
[0165] The aging resistance of the gas barrier film materials prepared in Application Examples 1-6 was tested:
[0166] According to the national standard GB / T 3512-2014, the samples were placed in an electric constant temperature blast drying oven, the aging temperature was set to 140°C, and the thermal oxygen aging time was 24h. The surface of the original and aged samples of PU and DBHP-LDH were tested and characterized by Fourier transform infrared spectroscopy, and the test range was 400-4000cm -1 , scan times 32 times.
[0167] Depend on Figure 8 It can be seen that the -OH absorption peak of the film material is enhanced after the addition of MgAl-DBHP-LDH obtained in Example 1, indicating that the possibility of hydrogen bond formation has increased to a certain extent. After accelerated thermal aging at 140°C for 24h, the absorption peaks of PU and MgAl-DBHP-LDH / PU at 3300-3500cm -1 (-OH) and 1710-1750cm -1 The increase in the absorbance of the absorption peak of (C=O) proves the occurrence of thermal oxidative aging; the range of absorbance increase is reduced after the addition of MgAl-DBHP-LDH, indicating that the incorporation of MgAl-DBHP-LDH gives PU good aging resistance.
[0168] The structure, morphology, oxygen barrier performance and aging resistance of the gas barrier film material prepared by the present invention are tested, and the results show that after the hydrotalcite is compounded with the polyurethane, the gas barrier performance of the prepared film material is significantly improved, and it has good aging resistance.
[0169] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a hydrotalcite material, characterized in that: The method comprises the following steps: (1) subjecting the first mixed salt solution and the alkaline solution to a colloidal grinding nucleation reaction to obtain a hydrotalcite seed slurry; (2) mixing the second mixed salt solution, the slow-release precipitant, the anionic high molecular polymer and the high polarity polymer to obtain a mixed solution; (3) adding the mixed solution obtained in step (2) dropwise to the hydrotalcite seed slurry obtained in step (1) to react and obtain a hydrotalcite material; Wherein, the first mixed salt solution and the second mixed salt solution both contain soluble divalent metal salts and soluble trivalent metal salts, and the types and concentrations of the metal salts are the same.
2. The method according to claim 1, wherein: In the first mixed salt solution and the second mixed salt solution, the divalent metal cations M in the soluble divalent metal salt 2+ The trivalent metal cation M in the soluble trivalent metal salt 3+ The molar ratio is 2-4:1; Preferably, the solvent of the first mixed salt solution and the second mixed salt solution is deionized water containing 5-50 vol% tetrahydrofuran; Preferably, the divalent metal cation M 2+ The concentration is 0.2-2mol / L; Preferably, the divalent metal cation M 2+ Mg 2+ or Zn 2+ ; Preferably, the trivalent metal cation M 3+ For Al 3+ ; Preferably, the volume ratio of the first mixed salt solution to the second mixed salt solution is 1:3-6; Preferably, in step (1), the molar ratio of the alkali in the alkaline solution to the metal cation in the first mixed salt solution is 2:1; Preferably, the base is sodium hydroxide; Preferably, the hydrotalcite seed slurry in step (1) is heated to 100-140°C.
3. The method according to claim 1 or 2, wherein: In step (2), the slow-release precipitant is hexamethylenetetramine and / or urea; Preferably, the anionic high molecular polymer is at least one selected from sodium polyacrylate, sodium polystyrene sulfonate and sodium polymethacrylate; Preferably, the weight average molecular weight of the anionic polymer is 1000-20000; Preferably, the high polarity polymer is selected from at least one of polyethylene glycol, polyacrylamide, hydroxymethyl cellulose and polydopamine; Preferably, the slow-release precipitant and the trivalent metal cation M in the soluble trivalent metal salt 3+ The molar ratio is 4-10:1; Preferably, the concentration of the anionic high molecular polymer is 5-50 g / L, preferably 6.7-20 g / L, and more preferably 15-16 g / L; Preferably, the concentration of the high polarity polymer is 2-40 g / L, preferably 5-16.7 g / L, and more preferably 9-12 g / L.
4. The method according to any one of claims 1 to 3, wherein: In step (3), the dropping time is 6-10h; Preferably, after the dropwise addition is completed, the temperature is raised to 140-180° C. and the reaction is continued for 6-8 hours; Preferably, after the reaction is completed, the mixture is cooled to room temperature and the precipitate is washed to obtain the hydrotalcite material.
5. The method according to any one of claims 1 to 4, wherein: The method further comprises: (4) dispersing the hydrotalcite material obtained in step (3) in a mixed solution containing a strong acid and its salt to carry out an ion exchange reaction to obtain a corresponding acid radical hydrotalcite material; Preferably, the amount of the hydrotalcite material is 10-30 g / L; Preferably, in the mixed solution containing a strong acid and its salt, the concentration of the strong acid is 0.001-0.005 mol / L; Preferably, in the mixed solution containing a strong acid and its salt, the concentration of the salt is 0.2-2 mol / L; Preferably, the strong acid is nitric acid or hydrochloric acid; Preferably, the salt is selected from at least one of ammonium salt, sodium salt and potassium salt; Preferably, the conditions for the ion exchange reaction include: stirring; time of 12-24 hours.
6. The method according to claim 5, wherein: The method further comprises: (5) dispersing the hydrotalcite material obtained in step (4) in an antioxidant solution to react to obtain a modified hydrotalcite material; Preferably, the concentration of the antioxidant solution is 1-2 mol / L; Preferably, the antioxidant is selected from at least one of p-methoxycinnamic acid, salicylic acid, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, coumarin-3-carboxylic acid, cinnamic acid, benzotriazole-4-hydroxy-benzenesulfonic acid, 2-phenylbenzimidazole-5-sulfonic acid and 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid; Preferably, the solvent of the antioxidant solution is formamide; Preferably, the molar ratio of the antioxidant to the anions between the layers of the hydrotalcite material is 1-4:1; Preferably, the reaction conditions include: stirring; temperature of 80-120° C.; time of 3-12 h.
7. A hydrotalcite material or a modified hydrotalcite material obtained by the preparation method according to any one of claims 1 to 6; Preferably, the size of the hydrotalcite material or modified hydrotalcite material is 2-10 μm.
8. Use of the hydrotalcite material or modified hydrotalcite material according to claim 7 in preparing a gas barrier film; Preferably, the substrate of the gas barrier film is selected from at least one of polyurethane, polyvinyl chloride, polylactic acid, polypropylene and nitrile rubber.
9. A polyurethane gas barrier film comprising the hydrotalcite material or modified hydrotalcite material according to claim 7; Preferably, the content of the hydrotalcite material or modified hydrotalcite material in the film is 1-10 wt %.
10. A method for preparing the polyurethane gas barrier film according to claim 9, characterized in that: The method comprises: mixing a dispersion of a hydrotalcite material or a modified hydrotalcite material with a polyurethane dispersion, and drying to obtain a polyurethane gas barrier film; Preferably, the mixing conditions include: temperature of 40-60°C; time of 2-4h; Preferably, the solvent of the polyurethane dispersion is tetrahydrofuran or dimethyltetrahydrofuran.
Citation Information
Patent Citations
Transparent gas barrier film materials and production method thereof
CN104817710A
Modified hydrotalcite, preparation method and application thereof, stretchable gas barrier film and preparation method thereof
CN112724463A
Cited By
High-strength gas barrier polyurethane adhesive and preparation method thereof
CN122012003A